Antimicrobial Study of Green Synthesized Silver Nanoparticles (AgNPs) by Using Ageratina adenophora and its Characterization - Gautam, Surendra K.; Baid, Yasha; Magar, Pabita Thapa; Binadi, Tirtha Raj; Regmi, Bishow (International Journal of Applied Sciences and Biotechnology, 2021)
Green chemistry refers to the design of chemical product and processes that reduce or eliminate the generation of hazardous substances. Silver nanoparticles (AgNPs) were synthesized successfully from AgNO3 through a simple green synthetic route using Ageratina adenophora leaf extract which acts as both reducing and capping agents. As synthesized AgNPs were characterized with the help of X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. XRD study shows crystalline nature of silver nanoparticles and average particle size was calculated as 24 nm using Debye Scherrer equation. Functional group responsible for the reduction of silver ion was investigated using FTIR spectroscopy. Hydroxyl group, amine group, aliphatic amine group were detected from FTIR analysis. Further, the green synthesized nanoparticles were found to be highly toxic against bacteria: Bacillus subtilis and Escherichia coli showing zone of inhibition of 11 mm and 9 mm, respectively.Int. J. Appl. Sci. Biotechnol. Vol 9(2): 128-132.